SPIRITUALITAS THERESIA DARI KANAK-KANAK YESUS DAN WAJAH SUCI Studi atas Keterkaitan antara Pengenalan dan Penghayatan Spiritualitas Kongregasi Suster-Suster Abdi Kristus - Margareta Dwi Wahyuni (Jurnal Teologi (Journal of Theology), 2014)
The Congregation of the Sisters Servants of Christ (Abdi Kristus, AK) chose Saint Thrse of the Child Jesus as their second patron. The purpose of this choice was that the AK sisters follow her life in their life of prayer, communion as well as mission. To determine whether the sisters have been familiar with the simplicity of life and spirituality of Saint Thrse, the author conducted this extensive research. The results lead to the conclusion that the introduction of the spirituality of Saint Thrse of the Child Jesus still needs to be intensified with a study on her life, especially the life of prayer which is reflected in her autobiography and personal letters, particularly within the framework of the initial formation of the AK sisters.